THE IMPORTANCE OF CONTINUOUS TEACHER TRAINING FOR THE NEW TEACHING PROFILE: A BIBLIOGRAPHICAL REVIEW AND DATA ANALYSIS - Aldeni de O. Andrade, Maria; da Silva, Dinorá; de Medeiros Oliveira, Antúzia; Dalva da Silva Santos, Maria; Batista Leonez, Erasmo (Revista Gênero e Interdisciplinaridade, 2024)
This paper presented an analysis of the importance of continuous teacher education in the current context of education. It was discussed how the constant updating of professionals can contribute to the development of more effective and inclusive pedagogical practices, in addition to positively impacting student learning and diversity in the classroom. For this, a bibliographic review and field research was carried out with teachers at a public elementary school. The results pointed to the need for continuous investment in teacher training and a greater appreciation of the profession. Finally, suggestions were presented for future research, aiming to deepen the theme and develop more effective strategies of continuing education for education professionals.